MIXED SCHEME OF THE FINITE ELEMENT METHOD FOR CALCULATING CABLE SYSTEMS - Aleksandr Baenkhaev (International Journal for Computational Civil and Structural Engineering, 2024)
A methodology for constructing variational formulations and solving geometrically nonlinear mixed problems by the finite element method is considered using the example of equilibrium of a flexible tensile thread. The results of solving the model problem are presented.